Repositioning TH cell polarization from single cytokines to complex help - Tuzlak, Selma; Dejean, Anne S.; Iannacone, Matteo; Quintana, Francisco J.; Waisman, Ari; Ginhoux, Florent; Korn, Thomas; Becher, Burkhard (Nature immunology, 2021)
When helper T (T H ) cell polarization was initially described three decades ago, the T H cell universe grew dramatically. New subsets were described based on their expression of few specific cytokines. Beyond T H 1 and T H 2 cells, this led to the coining of various T H 17 and regulatory (T reg ) cell subsets as well as T H 22, T H 25, follicular helper (T FH ), T H 3, T H 5 and T H 9 cells. High-dimensional single-cell analysis revealed that a categorization of T H cells into a single-cytokine-based nomenclature fails to capture the complexity and diversity of T H cells. Similar to the simple nomenclature used to describe innate lymphoid cells (ILCs), we propose that T H cell polarization should be categorized in terms of the help they provide to phagocytes (type 1), to B cells, eosinophils and mast cells (type 2) and to non-immune tissue cells, including the stroma and epithelium (type 3). Studying T H cells based on their helper function and the cells they help, rather than phenotypic features such as individual analyzed cytokines or transcription factors, better captures T H cell plasticity and conversion as well as the breadth of immune responses in vivo. The T helper subset paradigm has been instrumental in informing our understanding of T cell diversity; however, modern single-cell analyses have revealed the limits of the concept. In their Perspective, Becher and colleagues propose an alternative framework in which to understand T helper diversity, based not on transcription factors and cytokines but rather physiological functionality.